2020
DOI: 10.1002/apj.2613
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cigarette butts/coal‐based porous carbon and its catalytic methane decomposition to hydrogen

Abstract: A new type of cigarette butts/coal-based composite porous carbon was prepared by potassium hydroxide chemical activation method and used for methane decomposition to hydrogen. The effects of mass mixing ratio of the used cigarette butts/coal and carbonization temperature on the surface properties and structure of carbon materials were studied. The results show that the optimal mass mixing ratio of cigarette butts/coal is 1:3, and the increase in temperature can promote the specific surface area of carbon mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Using anthracite, 22 weakly caking coal, and some low-rank long-flame coal and lignite 23,24 as raw materials, PC materials with different properties have been obtained. For example, Yan et al prepared a coal-based PC with a S BET of 2372 m 2 g −1 and a microporous rate of 93% using KOH activation.…”
Section: Introductionmentioning
confidence: 99%
“…Using anthracite, 22 weakly caking coal, and some low-rank long-flame coal and lignite 23,24 as raw materials, PC materials with different properties have been obtained. For example, Yan et al prepared a coal-based PC with a S BET of 2372 m 2 g −1 and a microporous rate of 93% using KOH activation.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, CB contains nearly 95% cellulose acetate fiber, which as a good carbonaceous precursor can be converted into porous carbon with mesoporous and microporous by a certain activation process [10,11]. Recently, some literatures have reported that the carbon material prepared from CB had the characteristics of rich surface oxygen-containing groups and developed pore structure, showing excellent adsorption performance [12]. For example, Troy et al [13].…”
Section: Introductionmentioning
confidence: 99%